Pengembangan Pembelajaran Student Teams Achievement Divisions (STAD)-Virtual Melalui Breakout Room pada Aplikasi Zoom Meeting - Budi Sasomo (PYTHAGORAS : Jurnal Program Studi Pendidikan Matematika, 2021)
This writing aims to develop STAD learning with virtual learning during the Covid-19 pandemic. The preparation of this article uses the literature review method to get the problem formulation. Furthermore, literature review is also used for data collection, discussion, and drawing conclusions and suggestions. The results of the literature review showed that the STAD-Virtual learning steps were 1) the stage of delivering the material was carried out in the main room of the zoom meeting. 2) The group division stage with us participants is carried out in the main zoom meeting room. 3) Group activity in the breakout room and educators to make observations by entering the breakout room of each group. 4) The stage of evaluating learning outcomes in the main room of the zoom meeting. 5) The best group award stage takes place in the main rooms at the zoom meeting. STAD-Virtual learning is expected to make virtual learning solutions that are more varied, creative and innovative.